Proses Pengambilan Keputusan pada Konsumen untuk Membeli Rumah dari PT X Berdasarkan Alasan Pro-Lingkungan Hidup - Chatu Septiana; Arundati Shinta; Eny Rohyati (Jurnal Psikologi, 2021)
This study aims to explore consumer’s decision-making process in buying house (permanent residence building), based on pro-environmental reasons. It is a rare research since most of research on house consumer behavior revealed that price and location were the most important reasons in buying house rather than pro-environment reason. This is a qualitative research and 2 female owners (wives) participated in this research. They have already lived in that real estate developed by the X house enterprise for 4 months. This research revealed that those consumers have 5 stages in making a decision i.e. able to identify their needs, able to seek relevant information, able to make alternative evaluation, purchasing decision, and post-purchase behavior. It was also revealedseveral points: (1) the second subject is more likely to be an impulsive consumer since the process of decision making was only 4 days compare to 1 month for the first subject. It was occurred that the second subject was more likely depression because of conflict with her mother in law. (2) The first subject was more likely to have environmental sensitivity than the second subject. It was reflected from her favor on a friendly environment septic tank.